A short review of numerical cloud-resolving models. Issue 1 (1st January 2017) - Guichard, Françoise; Couvreux, Fleur
Abstract: A cloud-resolving model (CRM) allows performing numerical simulations of convective clouds, such as shallow cumulus and stratocumulus, or storms and squall-lines with a resolution on the order of a few tens of metres to a few kilometres over a limited-area 4D (time and space) domain. The development of such models over the past decades is reviewed and their specific features are presented. The latter include a non-hydrostatic dynamic and parameterizations of sub-grid turbulence, microphysical and radiative processes. The capabilities of such models are discussed based on comparisons with observations and model-intercomparison studies. CRMs are used in a variety of ways, from the exploration of cloud phenomenology and process-understanding studies to the development of algorithms for satellite products, as well as to address climate issues and to develop convective and cloud parametrizations for large-scale weather and climate models. A few results illustrating this wide utilization are presented. The continuous increase of computer power induces rapid changes in modelling perspectives and therefore, influences the developments and applications of CRMs. This is discussed together with emerging scientific questions which will further benefit from CRM simulations.